Influenza A (H3N2) infection followed by anti-signal recognition particle antibody-positive necrotizing myopathy: A case report. (February 2021) - Iriki, Jun; Yamamoto, Kazuko; Senju, Hiroaki; Nagaoka, Atsushi; Yoshida, Masataka; Iwasaki, Keisuke; Ashizawa, Nobuyuki; Hirayama, Tatsuro; Tashiro, Masato; Takazono, Takahiro; Imamura, Yoshifumi; Miyazaki, Taiga; et al.
Highlights: A case of immune-mediated necrotizing myopathy after influenza virus infection. Muscle biopsy and autoantibody revealed anti-SRP antibody-positive myopathy. IMNM should be considered in prolonged muscle weakness following viral infections. Abstract: A 60-year-old Japanese woman presented with subacute progressive muscle pain and weakness in her proximal extremities. She was diagnosed with influenza A (H3N2) infection a week before the onset of muscle pain. At the time of admission, she exhibited weakness in the proximal muscles of the upper and lower limbs, elevated serum liver enzymes and creatinine kinase, and myoglobinuria. She did not manifest renal failure and cardiac abnormalities, indicating myocarditis. Electromyography revealed myogenic changes, and magnetic resonance imaging of the upper limb showed abnormal signal intensities in the muscles, suggestive of myopathy. Muscle biopsy of the biceps revealed numerous necrotic regeneration fibers and mild inflammatory cell infiltration, suggesting immune-mediated necrotizing myopathy (IMNM). Necrotized muscle cells were positive for human influenza A (H3N2). Autoantibody analysis showed the presence of antibodies against the signal recognition particle (SRP), and the patient was diagnosed with anti-SRP-associated IMNM. She was resistant to intravenous methylprednisolone pulse therapy but recovered after administration of oral systemic corticosteroids and immunoglobulins. We speculate that the influenza A (H3N2) infection might have triggered her IMNM. Thus, IMNM should be considered as a differential diagnosis in patients with proximal muscle weakness that persists after viral infections.